Etika Periklanan Digital: Studi Kasus pada Aplikasi CrushOn.AI - Devya Sabila Fadly; Najwa Rasyidah Manar; Muhammad Ramzy Rasyid; Miftahul Dzikri; Daniel Handoko (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2025)
Digital advertising has changed a lot, especially with the emergence of AI. AI allows companies to create more personalized and relevant ads, which improves the performance of their marketing campaigns. Significant ethical challenges must be addressed behind this innovation. One of the main issues is how AI can be used to generate unethical or even illegal content. This study uses a qualitative approach using a case study method on the CrushOn AI application that advertises on media platforms such as Meta. The results of the study showed that there were violations in the application because there were elements of pornography and porn action, considering that currently users of applications such as Instagram and Facebook are young teenagers, this is considered negative because it has violated the EPI book. There is a need for a clear ethical and regulatory framework for the use of AI technology in advertising. Collaboration with stakeholders, including advertisers and social media platforms, is essential to support ethical advertising practices.